Melanoma in the liver: Oxidative stress and the mechanisms of metastatic cell survival. (June 2021) - Obrador, Elena; Salvador, Rosario; López-Blanch, Rafael; Jihad-Jebbar, Ali; Alcácer, Javier; Benlloch, María; Pellicer, José A.; Estrela, José M.
Abstract: Metastatic melanoma is a fatal disease with a rapid systemic dissemination. The most frequent target sites are the liver, bone, and brain. Melanoma metastases represent a heterogeneous cell population, which associates with genomic instability and resistance to therapy. Interaction of melanoma cells with the hepatic sinusoidal endothelium initiates a signaling cascade involving cytokines, growth factors, bioactive lipids, and reactive oxygen and nitrogen species produced by the cancer cell, the endothelium, and also by different immune cells. Endothelial cell-derived NO and H2 O2 and the action of immune cells cause the death of most melanoma cells that reach the hepatic microvascularization. Surviving melanoma cells attached to the endothelium of pre-capillary arterioles or sinusoids may follow two mechanisms of extravasation: a) migration through vessel fenestrae or b) intravascular proliferation followed by vessel rupture and microinflammation. Invading melanoma cells first form micrometastases within the normal lobular hepatic architecture via a mechanism regulated by cross-talk with the stroma and multiple microenvironment-related molecular signals. In this review special emphasis is placed on neuroendocrine (systemic) mechanisms as potential promoters of liver metastatic growth. Growing metastatic cells undergo functional and metabolic changes that increase their capacity to withstand oxidative/nitrosative stress, which favors their survival. This adaptive process also involves upregulation of Bcl-2-related antideath mechanisms, which seems to lead to the generation of more resistant cell subclones.